Pediatric asthma and its relation to socio-demographic factors in Baghdad / Waqar Al -Kubaisy, Shatha Hussain Ali. and Dawood Al – Thamiri - Al -Kubaisy, Waqar; Hussain Ali., Shatha; Al – Thamiri, Dawood (Universiti Teknologi MARA Cawangan Selangor, 2017)
Asthma is one of the most common chronic diseases of children, causing a huge burden on family and society It‟s prevalence has risen sharply over the past 30 years in many parts of the world with large geographical variations. However, in Iraq there is no national database which could be obtained. Due to the increasing number of cases and the burden of this health problem we investigated the sociodemographic and other risk factors related to asthma among primary school children. Modified ISAAC questionnaires were completed by the parents of 2262 children randomly chosen. We found males having higher rat of asthma Bing male be more at risk of developing asthma steadily increasing (27.4%), (28.3%)and (39.5%) with increased (CR) crowding rate (<3, 5 - 5,and >5) respectively. only CR of >5 acts as a significant risk factor for asthma. Urbanization acts as significant risk for developing asthma.